Towards a computer aided diagnosis system dedicated to virtual microscopy based on stereology sampling and diffusion maps - Plancoulaine Benoit; Michels Jean-Jaques; Oger Myriam; Belhomme Philippe; Herlin Paulette (BMC, 2011)
Abstract An original strategy is presented, combining stereological sampling methods based on test grids and data reduction methods based on diffusion maps, in order to build a knowledge image database with no bias introduced by a subjective choice of exploration areas. The practical application of the exposed methodology concerns virtual slides of breast tumors.